2023
DOI: 10.1021/acs.jpca.3c02161
|View full text |Cite
|
Sign up to set email alerts
|

Does Twisted Molecular Structure Always Induce Intersystem Crossing? A Case Study with Near-IR Absorbing 1,8-Diazabicyclo[5.4.0]undec-7-ene-fused Naphthaldiimide

Abstract: Heavy atom-free organic chromophores showing absorption in the near-IR region with intersystem crossing (ISC) ability are important for applications in various fields, e.g., photocatalysis and photodynamic therapy. Herein, we studied the photophysical property of a naphthalenediimide (NDI) derivative, in which the NDI chromophore is fused with pentacyclic 1,8-diazabicyclo[5.4.0]­undec-7-ene (DBU), which shows a strong charge-transfer (CT) absorption band (S0 → 1CT transition) in the near-IR region of 600–740 n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 63 publications
0
3
0
Order By: Relevance
“…Furthermore, compound 53 exhibited a dark S 1 state, which is rare for a Bodipy chromophore. In another example, a diazabicyclo[5.4.0]undec-7-ene-fused NDI compound showed low ISC ability, although the geometry was significantly twisted . Thus, it is concluded that the ISC capability of twisted/fused molecules does not simply rely on the torsion of π-conjugated systems.…”
Section: Heavy-atom-free Pss and Their Application In Tta-ucmentioning
confidence: 99%
“…Furthermore, compound 53 exhibited a dark S 1 state, which is rare for a Bodipy chromophore. In another example, a diazabicyclo[5.4.0]undec-7-ene-fused NDI compound showed low ISC ability, although the geometry was significantly twisted . Thus, it is concluded that the ISC capability of twisted/fused molecules does not simply rely on the torsion of π-conjugated systems.…”
Section: Heavy-atom-free Pss and Their Application In Tta-ucmentioning
confidence: 99%
“…[20] Sometimes called twisting-induced triplet state population in the literature, [21] this elegant strategy is currently attracting significant attention, particularly for preparing the next generation of heavy-atomfree photosensitizers. [22]…”
Section: Introductionmentioning
confidence: 99%
“…[22][23][24] However, whereas in some cases a strong increase in the efficiency of ISC by twisting has been observed, other twisted molecules showed just the opposite effect, and it was pointed out that other factors also play an important role. [25][26][27][28] Such a well-known factor is the effect of so-called heavy atoms, [29,30] i. e., atoms with a large nuclear charge. As the velocities of the inner electrons approach a substantial fraction of the velocity of light, relativistic effects and, thus, SOC becomes large.…”
Section: Introductionmentioning
confidence: 99%